Numerical Simulation of the Dust Production and Transportation Law of an Intermediate Mine Heap - Huang, Zhian (ACS Omega, 2021)
[Image: see text] In view of the current serious dust generation and environmental pollution that occur during the unloading process of an intermediate mine heap, in this study, the flow field and dust migration law for an intermediate mine heap were simulated numerically. Based on the mathematical model of the flow field and dust field, a numerical simulation was used to obtain the impact airflow and dust distribution law under different unloading conditions. The effects of different factors on the impact airflow and dust were studied. It could be concluded that the maximum impact wind velocity and dust concentration increased with an increase in the unloading flow. When the heap height is 23 m, the relationship between the maximum impact wind velocity and unloading volume was v = 0.05124(M(p))(0.62584) and the relationship between the dust concentration and mine unloading flow was c = 7.05613(M(p))(0.35002). The smaller the ore particle size, the larger the impact airflow and the greater the dust concentration. The relationship between the maximum impact wind velocity and the particle size was v = 1.54000(d)(−0.23786). The relationship between the dust concentration and ore particle size was c = 30.45323(d)(−0.54273). The greater the maximum impact wind speed, the more the dust generated. The existence of natural wind flow will initially accelerate the speed of dust diffusion and increase the dust concentration, but with the increase in natural wind flow, the diffusion effect will gradually reduce the dust concentration. An increase in the mine heap height will cause the impact wind’s speed and influence range to continuously decrease but will only have a small effect on the dust concentration.